Dexmedetomidine alleviates cerebral ischemia‐reperfusion injury in rats via inhibition of hypoxia‐inducible factor‐1α - Wang, Yuan‐Qing; Tang, Yu‐Feng; Yang, Ming‐Kun; Huang, Xi‐Zhao (Journal of cellular biochemistry, 2019)
Dexmedetomidine (Dex) was reported to reduce ischemia‐reperfusion (I/R) injury in kidney and brain tissues. Thus, we aimed to study the role and mechanism of Dex in cerebral I/R injury by inhibiting hypoxia‐inducible factor‐1α (HIF‐1α) and apoptosis. First, I/R injury models were established. Six groups were assigned after different treatments: sham, I/R, I/R+Dex, I/R+2‐methoxyestradiol (2ME2) (HIF‐1α inhibitor), I/R+CoCl 2 (HIF‐1α activator), and I/R+Dex+CoCl 2 groups. Neurological function, cerebral infarction volume, survival, and apoptosis of brain cells were then analyzed. Besides, immunohistochemistry and Western blot analysis were used to detect the expression of HIF‐1α, BCL‐2[B‐cell leukemia/lymphoma 2] adenovirus E1B interacting protein 3 (BNIP3), B‐cell leukemia/lymphoma 2 (BCL2), BCL2[B‐cell leukemia/lymphoma 2] associated X (Bax), and cleaved‐caspase3 proteins in brain tissues. I/R rats showed cerebral infarction, increased neurological function score, number of terminal‐deoxynucleoitidyl transferase mediated nick end labeling (TUNEL)‐positive cells and HIF‐1α–positive cells as well as decreased neurons. Inhibition of HIF‐1α can reduce the apoptosis induced by I/R, and overexpression of HIF‐1α can aggravate apoptosis in brain tissue of I/R rats. Furthermore, activation of HIF‐1α expression blocks the inhibitory effect of Dex on neuronal apoptosis in I/R rats. Dex may inhibit the neuronal apoptosis of I/R rats by inhibiting the HIF‐1α pathway and then improve the cerebral I/R injury in rats. Dexmedetomidine (Dex) can reduce apoptosis induced by cerebral ischemia‐reperfusion (I/R). Increased expression of hypoxia‐inducible factor‐1α (HIF‐1α) was found in brain tissue of I/R rats. Inhibition of HIF‐1α reduces apoptosis induced by I/R.